Reviewing Competence in Practice: Reform of Continuing Professional Development for Irish Pharmacists - Kennedy, Mary-Claire (Pharmacy (Basel), 2019)
There has been significant reform of the Continuing Professional Development (CPD) requirements for Irish pharmacists over the past five years. In 2015, a new system was established that includes quality assurance of practitioner engagement in CPD and quality assurance of practitioner competence. Pharmacists must now plan and document their learning activities in an electronic portfolio (ePortfolio) and they must participate in an ePortfolio Review process once every five-year period. A random sample is chosen each year to participate in a review of their practice for pharmacists in patient-facing roles. This paper provides an overview of the development and implementation of these quality assurance processes and it considers the outcomes that were observed in the first four years of implementation. By April 2019, almost 3000 pharmacists had participated in the ePortfolio Review process over the preceding three years, of which 96.2% demonstrated appropriate engagement in CPD. In the preceding two years, almost 200 pharmacists had participated in Practice Review, of which 97.5% have demonstrated the required level of competence across four competencies. All of the pharmacists who did not demonstrate the required level of competence in one or more competency area during Practice Review had previously demonstrated appropriate engagement in CPD through the ePortfolio Review process. This raises interesting questions regarding the use of engagement in continuing education (CE) or CPD as a surrogate measure for competence by professions.